Type synthesis of a family of novel parallel leg mechanisms driven by a 3-DOF drive system. (January 2022) - Li, Luquan; Fang, Yuefa; Yao, Jiaqiang; Wang, Lin
Highlights: A new synthesis method for the 3-DOF parallel leg mechanism is presented. Satisfactory 2-DOF walking mechanisms are synthesized by lie group theory. Novel 3-DOF PLMs are modularly designed with 3-DOF DSs and walking mechanisms. Performance analysis reveals the potential merits of novel PLM. Abstract: The complex structures, small workspaces and complex control systems of traditional parallel mechanisms are the largest hurdles to using them as leg mechanisms in walking robots. This paper synthesizes a family of novel 3-degrees-of-freedom (DOF) parallel leg mechanisms (PLMs) that have the potential to avoid these drawbacks. The novel parallel leg mechanism consists of a 3-DOF drive system (DS) and a walking mechanism, which can be designed modularly. Using the motion characteristics of the 3-DOF drive system, a simplified method for constructing 3-DOF parallel leg mechanisms is presented. Then, satisfactory 2-DOF walking mechanisms are synthesized based on Lie group theory. A family of novel 3-DOF parallel leg mechanisms in which the workspace of the foot-endpoint is a three-dimensional volume is constructed using the 3-DOF drive systems and 2-DOF walking mechanisms. Finally, the performance of the novel parallel leg mechanism is analysed, revealing the potential merits of this novel parallel leg mechanism in walking robots.